Family History among Breast Cancer Patients Attending the National Cancer Centre in Benghazi - Cross-Sectional Study. - Elsaid , Amina; Alfalah, Walaa; Boker , Sondos; Alesawi, Alesawi (Libyan Journal of Medical Research, 2026)
Background: Breast cancer (BC) is a type of cancer that develops in the cells of the breast. It is the most common cancer diagnosed in women worldwide, although it can also occur in men. Family history is a major risk factor for breast cancer. Familial breast cancer, defined by the clustering of cases within a pedigree, accounts for roughly 20% to 30% of all diagnoses, while high-penetrance germline mutations in genes such as BRCA1 and BRCA2 contribute to 5% to 10% of the total burden. Aim: To determine the percentage of family history of breast cancer among patients attending the National Cancer Centre of Benghazi. Methodology: A cross-sectional study was conducted using convenience sampling of all patients with files during 2023. Results: A total of 124 female patients, of whom 34% were aged 46 to 55 and 28% aged 36 to 45. The mean age of patients was 51.8 ±11.6, the minimum age was 31, and the maximum age was 81. 55% had a family history of breast cancer. Conclusion: This study highlights the significant presence of family history among breast cancer patients attending the National Cancer Centre of Benghazi. More than half of the patients (55%) reported a positive family history of breast cancer, suggesting that hereditary factors may play an important role in the occurrence of the disease among this population. These results emphasise the importance of increasing awareness about family history as a major risk factor for breast cancer and highlight the need for improved screening, early detection programs, and genetic counselling for women with a positive family history to reduce the burden of the disease.
Keywords: Percentage; Breast cancer; Family history; Benghazi